TINGKAT KETAHANAN PANGAN RUMAH TANGGA NELAYAN DI DESA SUKAJAYA LEMPASING KECAMATAN TELUK PANDAN KABUPATEN PESAWARAN - Defline Putri Delly; Fembriarti Erry Prasmatiwi; Rio Tedi Prayitno (Lampung University, 2019)
The aim of this research are to analyze the level of food security, the factors that affect the level of food security, and efforts to increase the level of food security of fisherman household. The location of this research is chosen purposively in Sukajaya Lempasing Village, Teluk Pandan Subdistrict, Pesawaran Regency in which respondents are 51 fisherman households. The data of this research was primary data and secondary data, collected in February – May 2018 and analyzed by cross-classification between the share of food expenditure and energy adequacy level, ordinal logistic regression, and descriptive qualitative analysis. The results of the research showed that the majority of respondent (68.63%) were classified as less food, and the rest were classified as food secure (13.73%), vulnerable to food (5.88%), and food insecure (11.76%). The affecting factors on the level of food security were formal education level of housewives and household food expenditure. The efforts to increase the level of food security by Government were through monitoring food availability and food reserves, developing food distribution and stabilization of food prices, Program Keluarga Harapan (PKH), and Raskin. Whereas, the efforts by fisherman household themselves were food loan (92.16%) and changing dietary habit (7.84%).Key words: cross-classification, fisherman household, food security